Narrative Review of Anti-Retrovirals Used in COVID-19 Treatment - Aditya Sindu Sakti; Irma Susanti; Djati Wulan Kusumo (Journal Clinical Pharmacy and Pharmaceutical Science, 2024)
The COVID-19 pandemic has necessitated the exploration of various therapeutic strategies, including the repurposing of existing antiviral drugs. This narrative review examines the use of anti-retroviral agents in the treatment of COVID-19, focusing on their mechanisms of action, efficacy, and safety profiles. Key antiretrovirals discussed include Remdesivir, Lopinavir/Ritonavir, Ribavirin, Oseltamivir, Favipiravir, and Sofosbuvir. These agents primarily act by inhibiting RNA-dependent RNA polymerase (RdRp), a critical enzyme in the replication cycle of SARS-CoV-2. Clinical trials and in vitro studies have provided mixed results regarding their effectiveness, with some agents showing promise in reducing mortality and improving recovery times, while others have demonstrated limited efficacy. The review highlights the urgent need for further clinical research to optimize antiviral regimens and improve patient outcomes in the ongoing battle against COVID-19.